Effect of equated continuous and interval running programs on endurance performance and jump capacity - Tuimil, J. L.; Boullosa, D. A.; Fernandez-del-Olmo, M. A.; Rodriguez, F. A. (The Journal of Strength and Conditioning Research, 2011)
We evaluated the effect of 2 different interval and continuous training programs on the maximal aerobic speed (MAS), time limit at MAS (Tlim), and on the countermovement jump (CMJ). Twenty-two physically active men were randomly distributed in an interval training group (ITG), continuous training group (CTG), and control group. The CTG and ITG performed 2 different training programs (65-70 and 90-100% of the MAS for CTG and ITG, respectively) that consisted of 3 sessions per week during a period of 8 weeks with an identical external workload (% MAS × duration in minutes). The MAS, the Tlim and the CMJ were recorded before and after the running training programs. The data analysis showed a significant and similar improvement (p < 0.01) of the MAS for both the ITG (5.8%) and CTG (8.3%). The Tlim and CMJ did not change significantly for either group after the training period. Our results indicate that 8 weeks of continuous or interval running programs with externally equated load led to similar improvements in the MAS without changing Tlim and CMJ performance in moderately trained nonrunners.